Clinical ethics support services during the COVID-19 pandemic in the UK: a cross-sectional survey. Issue 10 (9th November 2021) - Dittborn, Mariana; Cave, Emma; Archard, David
Abstract : Background: The COVID-19 pandemic highlighted the need for clinical ethics support provision to ensure as far as possible fair decision making and to address healthcare workers' moral distress. Purpose: To describe the availability, characteristics and role of clinical ethics support services (CESSs) in the UK during the COVID-19 pandemic. Method: A descriptive cross-sectional online survey was developed by the research team. The survey included questions on CESSs characteristics (model, types of support, guidance development, membership, parent and patient involvement) and changes in response to the pandemic. Invitations to participate were widely circulated via National Health Service institutional emails and relevant clinical ethics groups known to the research team. Results: Between October 2020 and June 2021, a total of 53 responses were received. In response to the pandemic, new CESSs were established, and existing provision changed. Most took the form of clinical ethics committees, groups and advisory boards, which varied in size and membership and the body of clinicians and patient populations they served. Some services provided moral distress support and educational provision for clinical staff. During the pandemic, services became more responsive to clinicians' requests for ethics support and advice. More than half of respondents developed local guidance and around three quarters formed links with regional or other local services. Patient and/or family members' involvement in ethics discussions is infrequent. Conclusions: The pandemic has resulted in an expansion in the number of CESSs. Though some may disband as the pandemic eases, the reliance on CESSs during the pandemic demonstrates the need for additional research to better understand the effectiveness of their various forms, connections, guidance, services and modes of working and for better support to enhance consistency, transparency, communication with patients and availability to clinical staff.